Co2+ doped Tio2 nanotubes visible light photocatalyst synthesized by hydrothermal method for menthyl orange degradation - Mohd Hasmizam Razali; Ahmad Fauzi Mohd Noor; Mahani Yusoff (IRJET, 2015)
Co2+ doped TiO2 nanotubes was successfully synthesized using simple hydrothermal method. The synthesized doped TiO2 nanotubes were characterized by X-ray diffractometer (XRD), transmission electron microscopy (TEM), energy dispersive X-ray spectroscopy (EDX) and ultra violet diffuse reflectance spectroscopy (UV-DRS) for band gap measurements. XRD pattern shows that after Co ion doping the phase structure of anatase TiO2 nanotubes transformed to hexagonal TiO2 with the nanotubes morphology remained as proved by TEM micrographs. The band gap energy of Co2+ doped TiO2 nanotubes gave as low as 2.06 eV compared to undoped TiO2 nanotubes (3.20 eV). This resulted Co doped TiO2 nanotubes exhibited higher rate for methyl orange degradation (MO) than the undoped TiO2 nanotubes.